Management of aortic aneurysm presenting during pregnancy: A case report. (March 2020) - Keepanasseril, Anish; Thendral, N; Dorairajan, Gowri; Subbaih, Murali; Pillai, Ajith Ananthakrishna; Sai Chandran, BV
Aortic aneurysm in pregnancy is associated with higher risk of complications due to the stress induced by the physiologic changes in pregnancy. Many of the reports are concentrated on those with catastrophic outcomes or who underwent surgical repair during pregnancy/puerperium. We report a case of aortic aneurysm, who presented during the second trimester and had a successful pregnancy outcome, and discuss the various issues concerning the management during pregnancy.